Cathepsin F cysteine protease of the human liver fluke, Opisthorchis viverrini. - Porntip Pinlaor; Natthawut Kaewpitoon; Thewarach Laha; Banchob Sripa; Sasithorn Kaewkes; Maria E Morales; Victoria H Mann; Sandi K Parriott; Sutas Suttiprapa; Mark W Robinson; Joyce To; John P Dalton; et al. (Public Library of Science (PLoS), 2009)
The liver fluke Opisthorchis viverrini is classified as a class I carcinogen due to the association between cholangiocarcinoma and chronic O. viverrini infection. During its feeding activity within the bile duct, the parasite secretes several cathepsin F cysteine proteases that may induce or contribute to the pathologies associated with hepatobiliary abnormalities.Here, we describe the cDNA, gene organization, phylogenetic relationships, immunolocalization, and functional characterization of the cathepsin F cysteine protease gene, here termed Ov-cf-1, from O. viverrini. The full length mRNA of 1020 nucleotides (nt) encoded a 326 amino acid zymogen consisting of a predicted signal peptide (18 amino acids, aa), prosegment (95 aa), and mature protease (213 aa). BLAST analysis using the Ov-CF-1 protein as the query revealed that the protease shared identity with cathepsin F-like cysteine proteases of other trematodes, including Clonorchis sinensis (81%), Paragonimus westermani (58%), Schistosoma mansoni and S. japonicum (52%), and with vertebrate cathepsin F (51%). Transcripts encoding the protease were detected in all developmental stages that parasitize the mammalian host. The Ov-cf-1 gene, of approximately 3 kb in length, included seven exons interrupted by six introns; the exons ranged from 69 to 267 bp in length, the introns from 43 to 1,060 bp. The six intron/exon boundaries of Ov-cf-1 were conserved with intron/exon boundaries in the human cathepsin F gene, although the gene structure of human cathepsin F is more complex. Unlike Ov-CF-1, human cathepsin F zymogen includes a cystatin domain in the prosegment region. Phylogenetic analysis revealed that the fluke, human, and other cathepsin Fs branched together in a clade discrete from the cathepsin L cysteine proteases. A recombinant Ov-CF-1 zymogen that displayed low-level activity was expressed in the yeast Pichia pastoris. Although the recombinant protease did not autocatalytically process and activate to a mature enzyme, trans-processing by Fasciola hepatica cathepsin L cleaved the prosegment of Ov-CF-1, releasing a mature cathepsin F with activity against the peptide Z-Phe-Arg-NHMec >50 times that of the zymogen. Immunocytochemistry using antibodies raised against the recombinant enzyme showed that Ov-CF-1 is expressed in the gut of the mature hermaphroditic fluke and also in the reproductive structures, including vitelline glands, egg, and testis. Ov-CF-1 was detected in bile duct epithelial cells surrounding the flukes several weeks after infection of hamsters with O. viverrini and, in addition, had accumulated in the secondary (small) bile ducts where flukes cannot reach due to their large size.A cathepsin F cysteine protease of the human liver fluke O. viverrini has been characterized at the gene and protein level. Secretion of this protease may contribute to the hepatobiliary abnormalities, including cholangiocarcinogenesis, observed in individuals infected with this parasite.